An Application of CNN-based Models with Fine-tuning Techniques on Malevis Malware Dataset - Tran, Hoang Hai (Vietnam-Korea University of Information and Communication Technology, 2024)
Proceedings of the 13th International Conference on Information Technology and Its Applications (CITA 2024); pp: 210-222